CAN MUSIC LIKES IN FACEBOOK DETERMINE YOUR PERSONALITY? - Managuran, Kala Devi; Varathan, Kasturi Dewi; Derhem Al-Garadi, Mohammad Ali (Malaysian Journal of Computer Science, 2021)
The ‘like’ icon is the most frequently used among all icons on Facebook. Although this social media platform is used by many people to express their music preferences publicly, Facebook ‘likes’ are still underutilised in determining personality. Thus, music ‘likes’ was employed in this study to gauge the personality of individuals based on a model that was developed by mapping music genres and personality traits. A computational technique that gauges users’ personalities on the basis of their music ‘likes’ on Facebook was also introduced. Results discovered that personality traits based on music preferences on Facebook assisted in revealing the personality of individuals. Furthermore, similar patterns in personality traits were obtained from a manual test, i.e., the Big Five inventory test performed on each respondent. Music genres and personality traits were mapped by the proposed model to examine the relationship between these two variables and the findings revealed that music ‘likes’ can be utilised to identify the personality of individuals.